Globalization and the changing trade debate: Suggestions for a new agenda - Thomas I. Palley (Levy Economics Institute of Bard College, 2007)
The failure of the Doha Development Round of World Trade Organization (WTO) negotiations in July 2006 was the first major collapse of a multilateral trade round since World War II. Research Associate Thomas Palley sees the failure as an event that could mark the close of a 60-year era of trade policy largely centered on increasing market access and reducing tariffs, quotas, and subsidies. Doha's demise represents an opportunity to challenge the intellectual dominance of the current WTO paradigm, to expose the failings of the neoliberal model of economic development, and to reposition the global trade debate.
Keywords: 330; Globalisierung; Internationale Handelspolitik; Welt